El proceso de transnacionalización y las relaciones externas de los países latinoamericanos - Tomassini, Luciano (Estudios Internacionales, 1984)
The transition from a world shaped by the relations between sovereign states to another characterized by the strengthening of transnational relations between the multiple segments that the different national societies present, probably constitutes the central tendency of the contemporary international system. In this paper, some considerations are formulated that could be useful to advance within the perspectives raised on this matter, based on three hypotheses: 1) the post-war international system is being replaced by another in which the concepts of interdependence and welfare predominate; 2) the crisis of industrial societies and the world economy as a whole strengthened the previous trend towards a recent interdependence, and 3) this process of transnationalization is profoundly altering the international relations of developing countries.